Comprehensive analysis of the circRNA expression profile and circRNA-miRNA-mRNA network in pelvic organ prolapse - Wang, Qian; He, Zuoxi; Ding, Lisha; Liu, Yuqing; Zhang, Xiaoli; Wang, Tao; Niu, Xiaoyu (Frontiers in Genetics, 2025)
Pelvic organ prolapse (POP) is a common gynecological disease caused by pathological defects, lesions, or mechanical weakening of the support structures of the pelvic floor. However, its pathogenesis is unclear. Circular RNAs (circRNAs) are covalently closed, endogenous biomolecules, which are thought to play an important role on skeletal muscle development by regulating gene expression. In this study, five pairs of peripheral blood samples from control and POP groups were used for circRNA sequencing analysis to obtain differential expression profiles. A total of 75 differentially expressed circRNAs (DEcircRNAs) were identified (fold change >2.0, P < 0.05). Furthermore, RT-qPCR confirmed that the expression levels of two circRNAs (hsa_circ_0067962 and hsa_circ_0057051) were significantly lower in the POP group. The two validated DEcircRNAs were abundantly involved in the collagen catabolic process. The circRNA-miRNA-mRNA network of two DEcircRNAs comprised nine mRNAs, which indicated that hsa_circ_0067962 and hsa_circ_0057051 may be involved in the pathogenesis of POP by regulating these nine mRNAs.